A scoping review of caries risk management protocols in Australia and New Zealand. (7th October 2018) - Amarasena, N; Haag, D; Peres, KG
Abstract: To identify and map the caries risk management protocols with multiple strategies, which were used in Australia and New Zealand and reported in the existing literature, a scoping review was carried out by electronically searching PubMed, Web of Science, Scopus, Embase and Dentistry and Oral Science. Studies on caries risk management protocols, written in English, limited to Australia and New Zealand and published up to March 2018 were included in the review. There was no restriction on participants' age. Of 257 studies identified, seven were included in the review. These seven studies were reported in Australia and all but six were based on the caries management system (CMS). There were two descriptive studies, one 3‐year multicentre cluster randomized controlled trial (RCT), one 2 to 4‐year post‐RCT follow‐up and two cost‐effective evaluations based on Markov decision analytic models. While concentrating on assessing individual behavioural risk factors for dental caries, studies indicated that the CMS would be more cost‐effective if its protocol was properly adhered to. Future studies on caries risk management protocols are suggested to consider both the individual characteristics and the social context of different population groups in view of enhancing the effectiveness of oral care.